GENERAL PURPOSE MICROWAVE CIRCUIT ANALYSIS USING MATLAB - MOHAMMED AHMED, LEENA ARSHAD (Universiti Teknologi Petronas, 2009)
The application of Computer Aided Design (CAD) is very crucial to microwave circuit design and analysis. The initial design of any arbitrarily microwave circuit must be simulated and verified prior to its fabrication. This eliminates the timeconsuming and costly changes on the fabricated circuit due to its limited ability to incorporate any modifications. There are many commercially available CAD packages that are used in industries and universities for fabrication and academic purposes. These packages are very sophisticated and reliable. However, a licensed microwave CAD package is very expensive for universities and colleges to obtain and use, especially for academic purposes. In this fmal year project, an attempt to develop a computer code that acts as a basis for an alternative CAD program for microwave network design and analysis is incorporated. The CAD program is to be developed specially to suit the learning requirements and outcomes of Microwave Engineering courses at universities and colleges. This report gives a general review on microwave circuits and their representations. In addition, it demonstrates the method chosen to perform the analysis on an arbitrary connected microwave network; Scattering Connection Matrix method. The report also details the procedure followed to develop the required computer code based on the chosen method. The computer codes are developed using Mathematics Laboratory (Matlab) software package. A detailed discussion and verification of the results obtained is also shown in this report. The results are verified using a sophisticated microwave CAD package called Advanced Design System (ADS) and compared with the results obtained from implementing the developed computer codes. Comparison of both results shows an acceptable accuracy between them and thus proves that the chosen method to analyze microwave networks is very effective and reliable.